2022
DOI: 10.3389/fpsyg.2022.993637
|View full text |Cite
|
Sign up to set email alerts
|

Hands-on childcare garden intervention: A randomized controlled trial to assess effects on fruit and vegetable identification, liking, and consumption among children aged 3–5  years in North Carolina

Abstract: Gardening at childcare centers may have a potent influence on young children’s learning about fruits and vegetables and their development of healthy dietary behaviors. This randomized controlled trial examined the effect of a garden intervention on fruit and vegetable (FV) identification, FV liking, and FV consumption among 3–5-year-old children enrolled in childcare centers in Wake County, North Carolina, USA. Eligible childcare centers (serving primarily low-income families) were randomly selected and then r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Analyzing data at these three levels makes this study unique compared to other relevant contemporary studies. The NC study [10] investigated similar effects only during school time (accelerometers were taken off before leaving childcare facilities), but it emphasized the need for investigating potential 'spillover effects' beyond school time at home. This study attempted to investigate this 'spillover effect' [28] by collecting PA data of children beyond school time while they were engaged in hands-on gardening at their respective childcare centers (experimental group).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analyzing data at these three levels makes this study unique compared to other relevant contemporary studies. The NC study [10] investigated similar effects only during school time (accelerometers were taken off before leaving childcare facilities), but it emphasized the need for investigating potential 'spillover effects' beyond school time at home. This study attempted to investigate this 'spillover effect' [28] by collecting PA data of children beyond school time while they were engaged in hands-on gardening at their respective childcare centers (experimental group).…”
Section: Discussionmentioning
confidence: 99%
“…Hands-on gardening, which is found to be associated with higher levels of PA for adults [6,7] and school-agers [8,9] can also be an effective intervention-based obesity prevention technique during early childhood. Two recent studies conducted in North Carolina (NC) [10,11] found positive associations between hands-on gardening and both PA and healthy eating preferences for preschoolers attending centerbased childcare. These are among the very few studies that investigated the potential role of gardening in licensed center-based childcare facilities for preventing obesity during the early years of childhood.…”
Section: Introductionmentioning
confidence: 99%
“…This study employed a waitlist-control group, RCT, to assess the impact of the Preventing Obesity by Design (POD) Gardening intervention [46] on PA among 3-5-year-old children enrolled in 15 ECEs in Wake County, North Carolina. The larger study also examined the effects of the intervention on children's fruit and vegetable identification, liking, and consumption [28]. The protocol is detailed elsewhere [47] and described briefly here.…”
Section: Methodsmentioning
confidence: 99%
“…Fruit and vegetable (FV) gardens have the potential to affect children's health behaviors, including dietary intake [28,29] and PA [30,31], in addition to providing opportunities for pedagogical instruction in areas such as science, math, and language arts [32,33]. Gardening offers children a variety of activities involving a range of PA intensities from low (e.g., transplanting, mixing growing medium, harvesting), to moderate (e.g., weeding, mulching), to high intensity (e.g., digging, raking) [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Hands-on gardening, which is found to be associated with higher levels of PA for adults [6,7] and school-agers [8,9] can also be an effective intervention-based obesity prevention technique during early childhood. Two recent studies conducted in North Carolina (NC) 2 [10,11] found positive associations between hands-on gardening and both PA and healthy eating preferences for preschoolers attending center-based childcare. These are among the very few studies that investigated the potential role of gardening in licensed center-based childcare facilities for preventing obesity during the early years of childhood.…”
Section: Introductionmentioning
confidence: 99%